Responses of human gingival and periodontal fibroblasts to a low-zinc environment - Rudolf, Emil; Cervinka, Miroslav (Alternatives to laboratory animals, 2010)
Morphology, motility, proliferation rate and markers of oxidative stress in primary human gingival fibroblasts (GF) and periodontal ligamental fibroblasts (PDL-F) grown in zinc-deficient cultivation medium (ZDM), were studied over a 5-week culture period. A low-zinc environment effectively reduced the total, as well as the free, intracellular zinc content in both cell types, over the course of the experiment. Decreased intracellular zinc content resulted in altered cellular morphology, reduced motility, and rearrangement of actin and tubulin in the cytoskeleton. In addition, fibroblasts with low zinc content exhibited decreased proliferation, accompanied by changes in cell cycle distribution, expression of specific biochemical markers, increased oxidative stress and the activation of caspase-3. Supplementation of ZDM with exogenous zinc prevented the loss of intracellular zinc, while also restoring the morphology, cell proliferation and mitogenic signalling of the cultured cells. Moreover, such supplemented cells were protected against oxidative stress and cell death. Of the two primary cell cultures examined, GF were more sensitive to decreased intracellular zinc content, when compared to PDL-F. The results obtained suggest that the human primary cell cultures can be useful for the longer-term evaluation of the effects of nutritional factors originating from the environment.
Keywords: signální transdukce; Signal Transduction; Cell Division; Humans; periodontální vaz; Cell Cycle; kaspasy; Gingiva; Zinc; lidé; Caspases; zinek; Glutathione; gingiva; DNA Replication; pohyb buněk; Periodontal Ligament; replikace DNA; Cell Movement; glutathion; fibroblasty; buněčný cyklus; Fibroblasts; buněčné dělení